Data_Sheet_1_Development and application of a whole genome amplicon sequencing method for infectious salmon anemia virus (ISAV).pdf - Bjørn Spilsberg; Magnus Leithaug; Debes Hammershaimb Christiansen; Maria Marjunardóttir Dahl; Petra Elisabeth Petersen; Karin Lagesen; Eve M. L. Z. Fiskebeck; Torfinn Moldal; Mette Boye (2024)
Infectious salmon anemia (ISA) is an infectious disease primarily affecting farmed Atlantic salmon, Salmo salar, which is caused by the ISA virus (ISAV). ISAV belongs to the Orthomyxoviridae family. The disease is a serious condition resulting in reduced fish welfare and high mortality. In this study, we designed an amplicon-based sequencing protocol for whole genome sequencing of ISAV. The method consists of 80 ISAV-specific primers that cover 92% of the virus genome and was designed to be used on an Illumina MiSeq platform. The sequencing accuracy was investigated by comparing sequences with previously published Sanger sequences. The sequences obtained were nearly identical to those obtained by Sanger sequencing, thus demonstrating that sequences produced by this amplicon sequencing protocol had an acceptable accuracy. The amplicon-based sequencing method was used to obtain the whole genome sequence of 12 different ISAV isolates from a small local epidemic in the northern part of Norway. Analysis of the whole genome sequences revealed that segment reassortment took place between some of the isolates and could identify which segments that had been reassorted.